2011
DOI: 10.1007/s00436-011-2727-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro amoebicidal activity of ethanol extracts of Arachis hypogaea L., Curcuma longa L. and Pancratium maritimum L. on Acanthamoeba castellanii cysts

Abstract: Acanthamoeba castellanii causes amoebic keratitis which is a painful sight-threatening disease of the eyes. Its eradication is difficult because the amoebas encyst making it highly resistant to anti-amoebic drugs, but several medicinal plants have proven to be more effective than the usual therapy. This study aimed to evaluate the in vitro amoebicidal activity of ethanol extracts of Arachis hypogaea L. (peanut), Curcuma longa L. (turmeric), and Pancratium maritimum L. (sea daffodil) on A. castellanii cysts. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…Besides this, AgNPs synthesized from J. gossypifolia were able to prevent encystment of the trophozoites. In addition, many plant metabolites such as flavonoids and alkaloids are reported for their antiparasitic potential although the mechanism of action is not yet clear (El-Sayed et al, 2012). Currently available drugs are known to cause unwanted effects on the plasma membrane of ocular cells (Ehlers & Hjortdal, 2004) thus this combination of nanoparticles and plant metabolites may give rise to a broad spectrum of drugs that can be used in the treatment of Acanthamoba infection.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, AgNPs synthesized from J. gossypifolia were able to prevent encystment of the trophozoites. In addition, many plant metabolites such as flavonoids and alkaloids are reported for their antiparasitic potential although the mechanism of action is not yet clear (El-Sayed et al, 2012). Currently available drugs are known to cause unwanted effects on the plasma membrane of ocular cells (Ehlers & Hjortdal, 2004) thus this combination of nanoparticles and plant metabolites may give rise to a broad spectrum of drugs that can be used in the treatment of Acanthamoba infection.…”
Section: Discussionmentioning
confidence: 99%
“…They stated that cysts were more resistant to this suppressive effect (Karakuş, Malatyalı, Zengin, & Değerli, ). Again, the minimal inhibitory concentrations (MIC) of Arachishypogaea L. , Curcuma longa L., and Pancratium maritimum L., A. hypogaea of 100 mg/ml were checked at 24, 48, and 72 hr and C. longa was effective at 1 mg/ml in 48 hr, while P. maritimum was effective at 200 mg/ml in 72 hr (El‐Sayed, Ismail, Ahmed, & Hetta, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is an essential metabolite that has therapeutic benefits and can be found in Pancratium maritimum L. This compound and other similar alkaloids also exhibit antimalarial, antiviral, antineoplastic, and antiparasitic (against Encephalitozoon intestinalis) activity. 37,38 In addition, pancratistatin that was extracted and purified from the Pancratium littorale inhibited E. intestinalis infection without affecting host cells. 39 Another study conducted by El-Sayed et al 38 found pancratistatin to be responsible for the cysticidal activity of P. maritimum against Achantamoeba castellani.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 In addition, pancratistatin that was extracted and purified from the Pancratium littorale inhibited E. intestinalis infection without affecting host cells. 39 Another study conducted by El-Sayed et al 38 found pancratistatin to be responsible for the cysticidal activity of P. maritimum against Achantamoeba castellani. Pancratistatin at very low concentrations (< 1 mM) also induced apoptosis, specifically in a broad range of cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%